Understanding Digital Library Use among STEM and Non-STEM Students: Insights from PLS-SEM MGA - Sumithra, S.; Sakshi, Shivam (Indian Journal of Information Sources and Services, 2024)
Digitalization has transformed education globally, with Digital Library Remote Access (DLRA) services offering seamless access to literature and scientific resources. This study examines the factors influencing DLRA usage behavior in a prestigious Indian private higher education institution. Using a sample of 400 researchers and students, the research investigates the factors influencing DLRA adoption among STEM and Non-STEM respondents. The data were investigated employing Partial Least Squares – Structural Equation Modeling Multi-group Analysis using SmartPLS software version 3. Findings reveal notable variations in social influence, facilitating conditions, habit, and usage patterns of STEM and Non-STEM participants. The novel study contributes to library and information science literature as well as technology adoption literature by exploring the differences among the factors influencing DLRA adoption among STEM and Non-STEM researchers and students.